Ellie's redemption - Jebber, Molly (Jebber, Molly. Amish Charm Bakery series., 2019)
Ellie Graber couldn't be happier working at Amish Charm--and making good on a precious chance to reunite with her Amish community. Grief over her mother's death made her rebel and try the Englischer world, but now she's home to start again. And quiet, thoughtful Joel Wenger is one of the few willing to understand her as their unexpected friendship develops into something much more . . .But no matter how hard Ellie tries, Joel's mother resolutely refuses to approve of her--much less accept her as a potential daughter-in-law. And as painful misunderstandings and a beautiful rival for Joel's affections threaten to separate the couple for good, can they bridge the gap between distrust and faith to secure a lifetime of love?